The Influence of Transformational Leadership and the Physical Work Environment on Employee Performance, Mediated by Work Discipline in Tanjung Selor District - Robbi Setiawan; Mujahid Mujahid; Abdul Samad Arif; Syamsul Riyadi (Scieclouds Publishing, 2026)
This research uses a quantitative approach with a survey method. Data analysis is carried out using a Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) approach to test the relationships between variables both directly and indirectly. The population in this study includes all employees of the Tanjung Selor District Government, with the sampling technique using a census/sampling method according to the total population. Data were collected through questionnaires that had been tested for validity and reliability and then analyzed using multiple linear regression analysis. The results of the study indicate that transformational leadership does not have a significant effect on employee performance, which shows that leaders have not been able to provide inspiration, motivation, and individual attention to improve employee performance. The physical work environment also has a positive and significant effect on employee performance, indicating that a comfortable, safe, and adequate work environment supports increased work productivity. In addition, work discipline has a positive and significant effect on employee performance, reflecting that adherence to rules and work responsibilities plays an important role in achieving optimal performance. The physical work environment has a positive and significant effect on employee performance, where a comfortable, safe, and adequate work environment can support increased work productivity. In addition, work discipline is proven to have a positive and significant effect on employee performance, reflecting that adherence to rules and work responsibilities plays an important role in achieving optimal performance.